PENGARUH PENERAPAN GOOD GOVERNANCE DAN TOTAL QUALITY MANAGEMENT PADA KINERJA AUDITOR INTERNAL - Ariningsih, Ni Kadek Dwi (E-Jurnal Akuntansi, 2017)
Companies today require auditing services that have a good work to help conduct inspections and oversee the operations of the company. The purpose of this study was to analyze the influence of good governance and total quality management on the performance of auditors internal.Penelitian was conducted at PT. Simas Multifinance Bali Province with eight offices in 2016 with the number of auditors as many as 39 people as a sample through a saturated sample method. Data was collected by distributing questionnaires to 39 respondents through multiple linear regression analysis. Based on the analysis, the application of good governance and total quality management has a positive influence on the performance of internal auditors at. Simas Multifinance Bali Province. Through t test analysis is known that good governance has a positive effect on the performance of internal auditors at. Simas Multifinance Bali Province. Total quality management has a positive influence on the performance of internal auditors at. Simas Multifinance Bali Province
Keywords: good governance, total quality management and performance of the internal auditor